2009
DOI: 10.1002/nau.20694
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RhoA mRNA and activated RhoA in urothelium and smooth muscle, and effects of a rho‐kinase inhibitor on contraction of the porcine urinary bladder

Abstract: The concentration of RhoA mRNA and activated RhoA enzyme were greater in urothelium than in detrusor. Y-27632 showed a stronger inhibitory effect in detrusor with intact urothelium than in dose without urothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…In immunolocalization with RhoA antibody, RhoA protein was observed predominantly in the detrusor smooth muscle, but to a lesser extent in the urothelium. This is in contrast to the finding by Nakanishi et al where the concentration of RhoA mRNA and activated RhoA enzyme were greater in the urothelium than in the detrusor 21 …”
Section: Discussioncontrasting
confidence: 99%
“…In immunolocalization with RhoA antibody, RhoA protein was observed predominantly in the detrusor smooth muscle, but to a lesser extent in the urothelium. This is in contrast to the finding by Nakanishi et al where the concentration of RhoA mRNA and activated RhoA enzyme were greater in the urothelium than in the detrusor 21 …”
Section: Discussioncontrasting
confidence: 99%
“…Part of the bladder contractility is independent of changes in [Ca 2þ ] i through the Rho/ Rho-kinase pathway and myosin phosphatase inhibition. 23 In fact, RhoA mRNA and activated RhoA enzyme have been identified in pig urothelium and detrusor. 23 In the present study, Y27632, a selective inhibitor of the Rho-associated protein kinase, reduced the ET-1-induced contraction, thus suggesting the involvement of a Rho/Rho-kinase pathway in such effect.…”
Section: Discussionmentioning
confidence: 99%
“…Rho kinase has been considered to be coupled to such excitatory receptors as muscarinic or α 1 ‐adrenoceptors 29,30 . ROCK and its activator RhoA are expressed in many tissues, including the urinary bladder, at mRNA and protein levels 3,4,11,15,18,19 . ROCK inhibitors reportedly reduce the potency of the muscarinic acetylcholine receptor agonist carbachol in the bladder, but results regarding carbachol efficacy are conflicting 9,11–19 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this pathway appears to take part in the contraction of non‐vascular smooth muscle at sites such as the rabbit bladder by modulating Ca 2+ sensitization and is thought to act by inhibiting myosin phosphatase activity 9,10 . Expression of Rho/ROCK and inhibition of muscle contraction by (+)‐(R)‐trans‐4‐(1‐aminoethyl)‐N‐(4‐pyridyl)cyclohexanecarboxamide dihydrochloride (Y‐27632), a ROCK inhibitor, have been demonstrated in bladder smooth muscle of rats, rabbits, pigs and humans 11–19 . Although previous studies have indicated that ROCK inhibitors such as Y‐27632 and fasudil (HA‐1077) reduce the potency of muscarinic receptor agonists carbachol in the bladder, results regarding carbachol efficacy are conflicting 11–19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation